2015
DOI: 10.14202/vetworld.2015.251-256
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of efficacy and safety of glycopyrrolate - xylazine - propofol anesthesia in buffalo calves

Abstract: Aim:To evaluate the efficacy and safety of glycopyrrolate - xylazine - propofol anesthesia in buffalo calves.Materials and Methods:The study was conducted on six clinically healthy male buffalo calves, 6-12 months of age, and weighing between 130 and 170 kg. In all the animals; glycopyrrolate (0.01 mg/kg, IM), xylazine (0.1 mg/kg, IM) and 1% propofol as single bolus (1.5 mg/kg, intravenous), were administered. The parameters observed included behavioral changes, physiological; hematological and blood biochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…In the present study, serum globulin and albumin in all four groups showed non-significant decrease at various intervals during an observation period in comparison to the respective baseline values. Potliya et al (2015) also reported similar finding during premedication with glycopyrrolate and xylazine and induction with propofol. This decrease in serum globulin and serum albumin was might be attributable to haemodilution due to continuous fluid therapy during the entire period of observation and shifting of ECF to the intravascular compartment to maintain normal CO during anaesthesia.…”
Section: Effects Of Anaesthetic Protocol On Kidney and Liver Function...supporting
confidence: 66%
“…In the present study, serum globulin and albumin in all four groups showed non-significant decrease at various intervals during an observation period in comparison to the respective baseline values. Potliya et al (2015) also reported similar finding during premedication with glycopyrrolate and xylazine and induction with propofol. This decrease in serum globulin and serum albumin was might be attributable to haemodilution due to continuous fluid therapy during the entire period of observation and shifting of ECF to the intravascular compartment to maintain normal CO during anaesthesia.…”
Section: Effects Of Anaesthetic Protocol On Kidney and Liver Function...supporting
confidence: 66%
“…DET at three doses (25, 50, and 75 μg/kg, IV) proves to produce sedation and analgesia in a dose‐dependent manner (El‐Maghraby & Al‐Qudah, 2005). In clinical practice, PRO is usually combined with other analgesic agents such as α 2 ‐adrenergic agonists or opioids to cover its analgesic shortage and short duration of action (Potliya et al, 2015). Induction of general anesthesia with PRO alone (2 mg/kg) or in a combination with either XYL (0.25 mg/kg) or DIAZ (0.25 mg/kg) was assessed.…”
Section: Alpha2‐adrenergic Agonists In Ruminantsmentioning
confidence: 99%
“…The maximum increase in duration of anesthesia along-with smooth induction, excellent muscle relaxation and smooth recovery may be probably attributable through a synergistic action of detomidinemidazolam with propofol-ketamine. The combinations of various pre-anesthetic had been used to prolong the duration of anesthesia along with shorter recovery time, thereby improving quality of anaesthesia (Potliya et al, 2015). Similar findings were also reported in calves (Kilic, 2008) and dogs (Sahoo et al, 2018).…”
Section: Discussionmentioning
confidence: 55%